Association between genetic variation on chromosome 9p21 and aneurysmal subarachnoid haemorrhage. Issue 4 (25th October 2010) - Olsson, Sandra; Csajbok, Ludvig Z; Jood, Katarina; Nylén, Karin; Nellgård, Bengt; Jern, Christina
Abstract : Background and aim: Genetic factors play a role in susceptibility to subarachnoid haemorrhage, but little is known about which genes are involved. Recently, genome wide association studies have identified the 9p21 region as a risk locus for intracranial aneurysms (IA). The aim of the present study was to examine the possible association between 9p21 and ruptured IA—that is, aneurysmal subarachnoid haemorrhage (aSAH)—in a Swedish population. There is one study showing an association between 9p21 and arterial stiffness, and arterial stiffness plays a role in the development of hypertension. Therefore, a second aim was to investigate whether a putative association is independent of hypertension. Methods: The study comprised 183 patients presenting with aSAH to the Neurointensive Care Unit at Sahlgrenska University Hospital and 366 healthy, age and sex matched population based controls. As the causative functional variant in the region has not yet been identified, a 44 kbp region on 9p21 was tagged using HapMap. Six single nucleotide polymorphism (SNPs) were genotyped. Results: Two SNPs, rs10757278 and rs1333045, showed significant associations with aSAH in univariate analyses. After adjustment for hypertension as well as for smoking, the association between aSAH and rs10757278 remained significant with an OR for aSAH of 1.42 (95% CI 1.08 to 1.87; p=0.01) for the uncommon G allele. Conclusions: These data confirm earlier results showing that 9p21 is a susceptibility locus for IA, and that this association is present in a Swedish sample restricted to ruptured IA. For the first time, it has been demonstrated that this association is independent of hypertension.